Electrical and mechanical properties of bismuth sodium potassium titanate doped with a modified barium titanate lead-free ceramics - Supalak Manotham (2020)
© 2019, © 2019 Taylor & Francis Group, LLC. Piezoelectric ceramics of bismuth sodium potassium titanate doped with a modified barium titanate (BNKT-xBTNb, x = 0.00–0.06) were prepared via the solid-state reaction process. The effect of BTNb on the phase formation, mechanical, dielectric, ferroelectric, and piezoelectric properties was investigated and discussed. All ceramics have a single perovskite phase. The data also revealed that there was a transformation from rhombohedral (x = 0.00) to mixed tetragonal/rhombohedral phases (0.02 ≤ x ≤ 0.04.), then to tetragonal-rich phases at x = 0.06. Microstructure analysis also indicated that the BTNb affected the morphology of the microstructure, where the average grain size decreased with increasing BTNb content. The BTNb doping produced an enhancement of mechanical properties, HV and HK increased with increasing BTNb content and reached the maximum values of 6.28 GPa, 5.51 GPa for x = 0.04 sample, respectively. The improvement of the properties was related to the change in microstructure. Furthermore, dielectric enhanced with increasing BTNb content, which reached a maximum value of 5439 for the x = 0.06 sample. However, the BTNb doping produced slimmer P-E loops which decreasing of Pr and Ec values. Meanwhile, the undoped BNKT displayed a highest piezoelectric coefficient, d33 of 198 pC/N.